Structure-based in silico investigation of antagonists of human ribonucleotide reductase from Annona muricata - Damilola A. Omoboyowa; Damilola S. Bodun; Jamiyu A. Saliu (Informatics in Medicine Unlocked, 2023)
Human ribonucleotide reductase (HRR) also known as ribonuceotide diphosphate reductase catalyzes the conversion of ribonucleotide to deoxyribonuceotides which is the rate limiting step in the synthesis of DNA, establishing the enzyme as a vital therapeutic target in discovery of cancer drugs. Hence, this study aimed at predicting HRR inhibitor(s) from Annona muricata bioactive compounds. A library of one hundred and twenty-six (126) compounds from Annona muricata was screened against HRR via the glide model. Eight (8) leads were used for the molecular mechanics generalized born surface area (MM-GBSA), e-pharmacophore, quantitative structural activity relationship (QSAR), pharmacokinetics profile and the top scored compound for molecular dynamics (MD) simulation using the Maestro - Schrödinger suite (2017-1). The quantum mechanics calculation of the lead compounds was carried out using Spartan 10. The results of the molecular docking and MM-GBSA calculation revealed eight (8) lead compounds observed as potent antagonists of HRR with binding affinity ranging from −6.454 kcal/mol to −10.190 kcal/mol which are comparable to the reference drug (Gemcitabine) and co-crystalized ligand. These eight hit compounds showed high fitness score and pIC50 value from the e-pharmacophore and QSAR analysis respectively. The result of the density functional theory of the hit compounds revealed that, EHOMO values range from −5.38 eV to −5.83 eV suggesting the hit molecules as electron donor. This study has predicted eight compounds from A. muricata as inhibitors of HRR with the stability of the top-scored compound (myricetin)-protein complex validated via MD simulation. Hence, in vivo and in vitro experiments are proposed for the discovery of potent therapeutic agents in the management of cancer via human ribonucleotide reductase inhibition.